An Exogenous NO Donor Provokes Mechanical Alternans in Normal Rat Atria and Impairs Sarcomere Contractility in Right Atrial Cardiomyocytes in Atrial Fibrillation - Xenia Butova; Tatiana Myachina; Polina Mikhryakova; Raisa Simonova; Daniil Shchepkin; Anastasia Khokhlova (Biomolecules)
Atrial fibrillation (AF) is the most common arrhythmia worldwide. AF is associated with a deficiency in nitric oxide (NO) production, which contributes to disturbances in the electrical and mechanical function of the atrial myocardium. NO donors are considered promising for the treatment and prevention of AF, but their effects on atrial contractility are unclear. This study examines the direct impact of a low-molecular-weight NO donor, spermine-NONOate (NOC-22), on the contractile function of atrial cardiomyocytes in paroxysmal AF. To study whether an NO donor-induced increase in NO level causes chamber-specific changes in atrial contractility, we measured sarcomere length (SL) dynamics in contracting single cardiomyocytes from the rat left and right atria (LA, RA) using a 7-day acetylcholine-CaCl2-induced AF model. We showed that in control rats NOC-22 provoked alternans of sarcomere shortening in both LA and RA cardiomyocytes. In AF, NOC-22 decreased the sarcomere-shortening amplitudes and velocities of sarcomere shortening–relengthening and increased the magnitude of sarcomere-shortening alternans only in RA cardiomyocytes. The negative effects of NO donors on RA contractility warrant careful consideration of their use in AF treatment.